QUANTIFYING THE EFFECTS OF BACTERIA ON ADSORPTION REACTIONS IN WATER-ROCK SYSTEMS - Fein J.B. (My University, 2000)
This paper reviews the investigations that quantify metal-bacteria, organic-bacteria, and bacteria-mineral adsorption reactions. The studies are divided into the two main approaches used to quantify adsorption: bulk partitioning approaches and surface complexation modeling. Partitioning adsorption models, such as ones which use Langmuir or Freundlich isotherms, are more simple to apply than surface complexation models because they do not require a detailed understanding of the nature of the surfaces or adsorption mechanisms involved. These measurements can be successful in describing adsorption/desorption processes for the conditions of interest if the conditions can be directly simulated in the laboratory. However, partition coefficients are applicable only to the conditions (pH, fluid and/or mineralogical compositions) at which they were determined. Conversely, surface complexation models describe adsorption reactions explicitly, accounting for surface and aqueous speciation changes as a function of pH and solution composition. The equilibrium constants which describe the extent of adsorption in surface complexation models are invarient with respect to the parameters which affect partition coefficients. This paper reviews the experimental studies which use surface complexation modeling to quantify the observed bacterial adsorption reactions. Although the number of studies is small, the results indicate that the surface complexation approach can successfully account for metal-bacteria, organic acid-bacteria, and bacteria-mineral adsorption reactions. Therefore, it offers a powerful means for estimating the effects of bacteria on solute adsorption over a wide range of subsurface conditions.
Keywords: BACTERIA; WATER; ROCK